Research Trends of Pharmacopuncture: a bibliometric analysis using VOSviewer (2007-2023) - Chan-Young Kwon (Korean Pharmacopuncture Institute, 2023)
Objectives: Pharmacopuncture is considered a unique new type of acupuncture in Korean medicine (KM). This study was performed to investigate the research trends regarding pharmacopuncture through a bibliometric analysis using VOSviewer.Methods : : The Web of Science Core Collection was searched for this study. The search terms were pharmacopuncture and pharmaco-puncture. The search was conducted on May 23, 2023, and 185 studies retrieved up to this date were included. Software VOSviewer version 1.6.19 was used to perform the bibliometric analysis. After data clearing, keyword co-occurrence and cooperation pattern analyses were performed.Results : : The number of studies on pharmacopuncture have gradually increased since the mid-2000s, with the most published in 2020 (46 studies). The quality of the studies has also steadily increased, and recently, several randomized controlled trials of pharmacopuncture have been conducted. Moreover, this treatment has been investigated in the context of KM clinical practice guideline development in Korea. The scope of pharmacopuncture studies to date seems to be limited to musculoskeletal pain and bee venom pharmacopuncture. The researchers from Jaseng Medical Foundation have been the core researchers in the field of pharmacopuncture in Korea. They collaborated with researchers from universities or government-funded research institutes. However, small-scale research teams from KM clinics and university researchers were also identified as independent clusters.Conclusion : : Pharmacopuncture research has grown both quantitatively and qualitatively, but the scope needs to be further expanded. There is also a gap between the use of pharmacopuncture by KM doctors in clinical settings and pharmacopuncture research. Based on these findings, some suggestions for future studies in this field are discussed. Furthermore, these findings may be used as data to expand and globalize pharmacopuncture research in the future.